2013
DOI: 10.1179/1465313313y.0000000066
|View full text |Cite
|
Sign up to set email alerts
|

Retention protocols and use of vacuum-formed retainers among specialist orthodontists

Abstract: VFRs were the most common retainer choice in the maxilla and mandible with full-time wear followed by part-time wear of RRs favoured by most. Full occlusal coverage with a thickness of 1.0 mm was the VFR design prescribed by the majority. More than one in six specialist orthodontists were aware that their patients used their VFRs as a receptacle for dental bleaching gel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 22 publications
(60 reference statements)
8
60
2
Order By: Relevance
“…An alternative literature search showed a lack of available literature on this topic. The number of retention check‐ups varies a lot in number and duration . Schneider et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative literature search showed a lack of available literature on this topic. The number of retention check‐ups varies a lot in number and duration . Schneider et al.…”
Section: Discussionmentioning
confidence: 99%
“…The number of retention check-ups varies a lot in number and duration. [5][6][7][8]55,67,68 Schneider et al (2011) and others showed that failure of fixed retainers is highest directly after the debonding of orthodontics appliances. 28,69,70 The combination of increased mobility together with increased failure risk within the first month after debonding indicates the first retention check-up should occur within the first three months post-treatment.…”
Section: Cq2 Which Frequency Of Retention Check-ups Is Advisable Fomentioning
confidence: 99%
“…The vacuum-formed retainer (VFR) is one of the most common types used in daily orthodontic practice. VFRs are removable, clear, transparent, and thermoplastic retainers that were first developed by Kesling in 1945(Kesling, 1945Meade and Millett, 2013). The VFRs were fabricated from elastic polymers and were the first attempt to introduce such material in the field of orthodontics.…”
Section: Introductionmentioning
confidence: 99%
“…All previous studies have evaluated perceptions on different groups, which reduces the importance of the comparisons. 4,5,6,7,8,9,12,13,14,15,16,17 The most commonly used maxillary orthodontic retainers are removable, especially the Hawley plate, the WA, and the CT, whose preferences vary according to country or region. 2,3,16,18,19,20,21,22,23 The WA was selected for this study in relation to the Hawley plate, because the aim was to evaluate the influence of the different palatal acrylic designs, and the occlusal interference generated by the Hawley retaining clasps could impair this evaluation.…”
Section: Discussionmentioning
confidence: 99%